Masjid Makam Mantingan Sebagai Aset Pariwisata Religi Di Jepara - Melya Milviana; Lintang Marsashi Kirana; Salsa Nabila Aisya Naya; Fauzan Syahru Ramadhan (Badan Riset dan Inovasi Nasional (BRIN), 2024)
This article focuses on examining the current condition and tourism management of the Mantingan Tomb Mosque in Jepara Regency. This research aims to analyze the potential of the Mantingan Cemetery Mosque as a religious tourism asset in Jepara Regency. This article uses observation and historical methods that include heuristics, criticism, interpretation, and historiography. The results show that although the physical condition of the Mantingan Cemetery Mosque is well maintained and has high historical value as a relic of Queen Kalinyamat in the 16th century, its tourism management is still not optimal. The management of the area carried out by the Mantingan Tomb and Mosque Complex Foundation is more focused on religious activities rather than tourism development. The management of Mantingan Tomb Mosque is still passive and minimal intervention, so a comprehensive development strategy is needed to optimize the potential of religious tourism that can boost the regional economy.